Evaluating the Validity and Reliability of the Knowledge, and Practice Questionnaire of Iranian Mothers About the Development of Persian-speaking Children Aged 18 to 36 Months - Zahra Valitabar Kerati; Morteza Farazi; Atieh Ashtari; Fatemeh Jazem; Majid Jannat (Iranian Rehabilitation Journal, 2023)
Objectives: The mother’s knowledge and attitude about the child’s developmental norms can affect their practice and the quality of parent-child interaction. The quality of a child’s development in the early years significantly impacts their personality and future success. Therefore, this study aims to develop and investigate the psychometric characteristics of the Iranian mother’s knowledge, attitude, and practice (KAP) questionnaire about the development of communication, language, speech, and swallowing of Persian-speaking children aged 18 to 36 months and comparing them. Methods: This study was a descriptive-analytical and cross-sectional study conducted on 280 mothers with typically developed children aged 18 to 36 months from different provinces of Iran. Due to the COVID-19 pandemic with the implementation of the study, the participants were selected as available, and then the snowball completed the questionnaire in both face-to-face and online methods. To check the validity of the questionnaire, face validity was calculated using the opinion of speech therapy experts and ten mothers, and content validity was calculated using the Lawshe method. To check the reliability of the questionnaire, the test re-test method was used in a two-week interval. Results: The results indicated that this questionnaire has high validity (content validity index [CVI] >0.79) and reliability (intraclass correlation coefficient [ICC]=0.90). The multiple linear regression model showed that only the mother’s age has a significant positive relationship with knowledge ([B=0.082] P=0.04) about the development of communication, language, speech, and swallowing of children aged 18 to 36 months. Socioeconomic status and the mother’s education had no significant relationship with the mother’s KAP. Also, this study showed that the mother’s knowledge, attitude, and practice about a child’s development were high (mean=16.5), positive (mean=56.44), and good (mean=60.27). Discussion: This study showed that the designed questionnaire is a valid and reliable tool that can be used to investigate the mother’s KAP about the development of communication, language, speech, and swallowing of Persian-speaking children aged 18 to 36 months. On the other hand, speech and language pathologists can use this questionnaire in related studies and clinical evaluations to have better and more knowledge of the child’s environment and the factors affecting it in Persian-speaking society.